Enteropathy Associated with Olmesartan - Silva,Bruno Moreira da (2016)
The recognition of an enteropathy caused by olmesartan is recent. It was first described in 2012 by the Mayo Clinic, which presented 22 clinical cases. Olmesartan is a highly prescribed drug and the differential diagnosis of a sprue-like enteropathy is very wide, so it is important to be aware of this pathology. We report a case of a 67-years-old man, with arterial hypertension under treatment with olmesartan, with a 4-months history of diarrhea and weight lost. He was admitted three times in our Department during this period of time. An initial diagnosis was made of lymphocytic colitis but he did not respond to treatment with corticosteroids. There was a high suspicion of celiac disease, so the patient started a gluten-free diet but still there were no symptomatic changes. The patient underwent several blood and imaging tests which were negative. Due to the suspicion of an enteropathy caused by drugs, olmesartan was stopped and the patient showed a significant improvement of his symptoms. The exact pathophysiology of this entity remains to be elucidated. It may affect all gastrointestinal tract and mimic a refractory celiac disease as well as a lymphocytic colitis due to similar symptoms and histology. It is expected more cases like this in the future due to high use of olmesartan in current clinical practice. So, it is important to all gastroenterologists to be aware of this pathology and take it into consideration when putting together a differential diagnosis.